Implementing quantum electrodynamics with ultracold atomic systems - Kasper, Valentin; Hebenstreit, Florian; Jendrzejewski, Fred; Oberthaler, Markus K.; Berges, Jürgen (New journal of physics, 2017)
We discuss the experimental engineering of model systems for the description of quantum electrodynamics (QED) in one spatial dimension via a mixture of bosonic 23 Na and fermionic 6 Li atoms. The local gauge symmetry is realized in an optical superlattice, using heteronuclear boson-fermion spin-changing interactions which preserve the total spin in every local collision. We consider a large number of bosons residing in the coherent state of a Bose-Einstein condensate on each link between the fermion lattice sites, such that the behavior of lattice QED in the continuum limit can be recovered. The discussion about the range of possible experimental parameters builds, in particular, upon experiences with related setups of fermions interacting with coherent samples of bosonic atoms. We determine the atomic system’s parameters required for the description of fundamental QED processes, such as Schwinger pair production and string breaking. This is achieved by benchmark calculations of the atomic system and of QED itself using functional integral techniques. Our results demonstrate that the dynamics of one-dimensional QED may be realized with ultracold atoms using state-of-the-art experimental resources. The experimental setup proposed may provide a unique access to longstanding open questions for which classical computational methods are no longer applicable.
Gesehen am 18.09.2017